(untitled) (Research, Society and Development, 2022)
Objective: Verifying the scientific evidence revealed by surveys of identify the profile of domestic violence against women (DVAW) in Brazil. Methodology: This is a descriptive study of the integrative review type of the literature. The use of the descriptors: “violence against women” AND “domestic violence”, applied in the following databases was established: Latin American and Caribbean Literature on Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Scientific Electronic Library Online (SCIELO). Complete articles related to the research object were included, in Portuguese, English and Spanish languages, indexed in these databases in the period between 2011 and 2021. Exclusion criteria for the sample were: review articles, dissertations, theses and research conducted in other countries. Results: The searches in the databases rescued a total of 415 articles, of which 12 were included in the sample. The predominance of studies published in 2017 was identified. In the studies, it was observed the characterization of the aggressor, as well as the type of violence perpetrated against women as the main findings in common. Conclusion: Scientific evidence has shown that the aggressor is usually male, where in most cases it is the spouse/partner of the woman. As for the profile of the type of DVAW perpetrated, psychological/moral violence prevails, followed by physical and sexual violence. In addition, the use of alcohol and other drugs by the partners, proved to be a triggering factor for The DVAW. It was noticed deficiency in the implementation of public health policies in the face of the disease.